The Influence of Online Learning in Improving The Literacy Competence of Primary Teacher Education (PGSD) Students in Universitas Negeri Semarang During The Epidemic Crisis - Isdaryanti, Barokah; Ahmadi, Farid; Wulandari, Desi; Sulistyorini, Sri (Journal of Research and Educational Research Evaluation, 2020)
Online learning is one of the innovations in education in respond to the development of technology nowadays that is to provide innovative learning source. It allows students to have more flexibility in learning since it can be done whenever and wherever they want it to be. They could interact with the lecturer through applications like e-classroom, video conference, zoom or even chat in whatsapp group. Online learning is also an innovation in education to imprve the literacy competence of students and encourages students to be able to do three critical analysis such as conducting interview, examining the environment, writing report, and doing observation well.This study aims at analyzing the proses of online learning conducted for the PGSD Unnes students and analyzing the influence of the learning on the improvement of their literacy competence throughout the pandemic crisis. The method implemented is mixed method that is conducting both parametric and non-parametric statistic analysis. It is started from quantitative data that is processed and tested using statistics test, continued by analyzing the data using descriptive qualitative method to portray the process and influence of online learning on the improvement of literacy competence of PGSD students during the pandemic. Based on the observation and questionnaire, it could be analyzed how much the students participate in the online larning process and literary activity during the pandemic. The samples in this research are the students of PGSD Universitas Negeri Semarang (UNNES). The data collected from the samples then being analyzed using statistics and descriptive test, presented and concluded.